Analysis Of Ethical And Medicolegal Aspects In Health Insurance In Indonesia: A Scoping Review Approach - Adji Suwandono; Dilma’aarij Agustia; Yudhistira Andarusukma (Green Publisher Indonesia, 2025)
Background: The National Health Insurance (Jaminan Kesehatan Nasional/JKN) managed by BPJS Kesehatan aims to provide equal access for the entire communities accross nation. However, its implementation faces various challenges related to ethical and medicolegal aspects, including service limitations, patient rights, and medical personnel responsibilities. Objective: The study aims to analyze the ethical and legal aspects within The National Health Insurance in Indonesia. Methods: This study uses the scoping review method with the PRISMA-ScR approach. Literature searches were conducted through the PubMed and Garuda databases using the keywords National Health Insurance, BPJS Health, Medical Ethics, and Medicolegal. Included articles were those published in the last 10 years and relevant to the topic of study. Results: Our result shows that some major challenges in health care services in Indonesia include limited health facilities, ease of access for communities in remote areas, and administrative challenges in BPJS claims. From an ethical standpoint, the principle of justice is often debated due to the uneven distribution of services. From a legal perspective, there is still ambiguity in the medicolegal responsibilities of health workers within the health insurance system, especially regarding medical disputes and legal obligations in BPJS-based services. Conclusion: The implementation of BPJS Kesehatan faces ethical, legal, administrative, and service quality challenges. Thus, policy evaluation, strengthened oversight, and improved legal protection and service quality are needed to strengthen the system